2017
DOI: 10.1038/srep40646
|View full text |Cite
|
Sign up to set email alerts
|

25(OH)D and 1,25(OH)D vitamin D fails to predict sepsis and mortality in a prospective cohort study

Abstract: The clinical role of vitamin D in sepsis and mortality prediction is controversially discussed. Therefore, we conducted a prospective cohort study on standard care wards, including 461 patients with suspected sepsis fulfilling two or more SIRS criteria. On the first and third day after onset of SIRS symptoms levels of 25(OH)D, 1,25(OH)D and sepsis biomarkers were analysed for their predictive capacity for identifying infection, bacteraemia and an elevated mortality risk. Additionally, several SNPs associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
2
12
0
1
Order By: Relevance
“…Serum 25(OH)D was less than 20ng/mL in 1,233 of 1,745 samples (70.7%), and 8.0% (139 of 1,745 samples) showed even less than 10 ng/mL which is characterized as severe vitamin D deficiency. Consistent with previous reports, there was a clear seasonal change with a peak at the end of summer and a trough in early spring[18] (Fig 3), both in allergic and non-allergic pregnant women (S1 and S2 Figs). The median level of serum 25(OH)D in each season was 15, 14, 19, and 20 ng/mL in winter (Dec-Feb), spring (Mar-May), summer (Jul-Aug) and autumn (Sep-Nov), respectively.…”
Section: Resultssupporting
confidence: 91%
“…Serum 25(OH)D was less than 20ng/mL in 1,233 of 1,745 samples (70.7%), and 8.0% (139 of 1,745 samples) showed even less than 10 ng/mL which is characterized as severe vitamin D deficiency. Consistent with previous reports, there was a clear seasonal change with a peak at the end of summer and a trough in early spring[18] (Fig 3), both in allergic and non-allergic pregnant women (S1 and S2 Figs). The median level of serum 25(OH)D in each season was 15, 14, 19, and 20 ng/mL in winter (Dec-Feb), spring (Mar-May), summer (Jul-Aug) and autumn (Sep-Nov), respectively.…”
Section: Resultssupporting
confidence: 91%
“…Researchers have reported that low plasma 25(OH)D at admission predicts unfavorable outcomes such as need for mechanical ventilation (Ardehali et al, 2018;Ebenezer et al, 2016), organ failure (Braun et al, 2011) Lucidarme et al, 2010), systemic bloodstream infection (Amrein et al, 2014;Braun et al, 2011), ICU-AI (Ebenezer et al, 2016;Quraishi et al, 2013), VAP (De Pascale et al, 2016;Vassiliou et al, 2018), and all-cause mortality (Braun et al, 2011;Moraes et al, 2015;Moromizato et al, 2014) in critically ill patients. However, others studies have shown no significant association of plasma 25(OH)D with unfavorable outcomes such as organ failure (Ala-Kokko et al, 2016), septic shock (Ratzinger et al, 2017;Shojaei et al, 2019), acute/severe sepsis (Ala-Kokko et al, 2016), systemic bloodstream infection (Moraes et al, 2015), ICU-AI (Ala-Kokko et al, 2016;Flynn et al, 2012;Kempker et al, 2015;Vosoughi et al, 2016), VAP (Flynn et al, 2012), and all-cause mortality (Alizadeh et al, 2015;Barnett et al, 2014;Cecchi et al, 2011;Kempker et al, 2015;Kvaran et al, 2016;Ratzinger et al, 2017;Vassiliou et al, 2018;Vosoughi et al, 2016) in critically ill patients. Likewise, researchers have reported that length of stay was (Alizadeh et al, 2015;Amrein et al, 2014;Ardehali et al, 2018;Ebenezer et al, 2016)…”
Section: Discussionmentioning
confidence: 99%
“…In contrary to our results, Gokhanet et al [ 29 ] reported that high serum 25-OH vitamin D levels are associated with pediatric sepsis, and this difference may be due to the age group and the different sample size. In addition, Ratzinger et al [ 30 ] reported that 1,25-OH D but not 25-OH D can predict bacteraemia and both of them failed to predict sepsis and mortality in a prospective cohort study, but this difference between our results and Ratzinger’s may be attributed to the age group of patients, as all of Ratzinger’s patients were above 41 years old, the different types of infections recruited in his study (respiratory, gastrointestinal (GIT), urological and central nervous system (CNS) infections), and, lastly, the methodology and the time for assay of vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%